Prognostic value of susceptibility-weighted imaging of prominent veins in acute ischemic stroke: A systematic review and meta-analysis - Xiang, Wei; Liang, Zhigang; Zhang, Manman; Wei, Hongchun; Sun, Zhongwen; Lv, Yaodong; Meng, Yuedan; Li, Wei; Zheng, Huaguang; Zhang, Hongxia (Frontiers in Neurology, 2022)
Background: The prominent veins sign (PVS) on susceptibility-weighted imaging (SWI) have been suggested to be related to the prognosis of patients with acute ischemic stroke (AIS). This meta-analysis aims to clarify the association between PVS and the prognosis of patients with AIS. Methods: This meta-analysis was registered in PROSPERO with the number CRD42022343795. We performed systematic research in PubMed, Web of Science, EMBASE, and Cochrane Library databases for studies investigating the prognostic value of PVS. Based on the enrolled studies, patients were divided into the with PVS cohort and without PVS cohort. Outcomes were the unfavorable functional outcome, early neurological deterioration (END), and hemorrhagic transformation (HT). The random-effects models were used for the meta-analytical pooled. Heterogeneity was estimated by using Cochran’s Q test and I2 value. Subgroup and sensitivity analyses were also performed to explore the potential sources of heterogeneity. Publication bias was assessed with funnel plots and assessed by Begger’s and Egger’s tests. Results: Nineteen studies with 1867 patients were included. PVS was were correlated with an unfavorable functional outcome in patients with AIS (RR = 1.61, 95% CI = 1.28–2.02), especially in those receiving recanalization therapy (RR = 2.00, 95% CI = 1.52–2.63), but not in those treated conservatively (RR = 1.33, 95% CI = 0.87–2.04). Moreover, PVS were related to END (RR = 2.77, 95% CI = 2.21–3.46), while without an increased risk of HT (RR = 0.97, 95% CI = 0.64–1.47). Conclusions: PVS were associated with an unfavorable prognosis of patients with AIS and increased the risk of END, while not correlated with an increased risk of HT. PVS might be useful for predicting functional outcomes of patients with AIS as a novel imaging maker.